Why are we here?: a phenomenological study of the University of Wisconsin - Stout's Master of Fine Arts in Design student body - Banasik, Daniel P. (University of Wisconsin--Stout, 2018)
This thesis project explores individual student journeys within the MFA in Design program at the University of Wisconsin - Stout. More specifically, this project examines what led each student to the program, their journey throughout the program and post-completion program goals. Qualitative design research, phenomenology, portraiture and design methodology play major roles in this exploration. The principal objectives for this project focus on three key areas of discovery. First, to develop and present individual "life in design" timelines for each MFA in Design student who participated in this research project as an example of portraiture. Second, to present the MFA in Design program from the student perspective in support of potential program improvements and future growth. And lastly, to explore, develop and present theories as to why an MFA in Design program was chosen for graduate studies. Based on extensive personal data evaluated, this project theorizes that no matter the rationale or justification, the current and recently graduated MFA in Design students at the University of Wisconsin - Stout are simply craving more. More education, more beyond design practice and more exposure to other designers and design disciplines. Everyone's passion for design defines their graduate school experience.
Keywords: Portrait drawing; Phenomenology; Graduate students